2012
DOI: 10.1002/stem.1131
|View full text |Cite
|
Sign up to set email alerts
|

Etv2 Is Expressed in the Yolk Sac Hematopoietic and Endothelial Progenitors and Regulates Lmo2 Gene Expression

Abstract: During embryogenesis, the endothelial and the hematopoietic lineages first appear during gastrulation in the blood island of the yolk sac. We have previously reported that an Ets variant gene 2 (Etv2/ER71) mutant embryo lacks hematopoietic and endothelial lineages, however, the precise roles of Etv2 in yolk sac development remains unclear. In the present study, we define the role of Etv2 in yolk sac blood island development using the Etv2 mutant and a novel Etv2-EYFP reporter transgenic line. Both the hematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 59 publications
4
95
0
Order By: Relevance
“…The Etv2 homozygous mutant embryos were lethal by E9.5, and lacked the endocardial/endothelial lineage [14]. Recent in vivo and in vitro results further support the hypothesis that ETV2 is a critical factor for the specification of the endocardial/endothelial and hematopoietic lineages [15,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…The Etv2 homozygous mutant embryos were lethal by E9.5, and lacked the endocardial/endothelial lineage [14]. Recent in vivo and in vitro results further support the hypothesis that ETV2 is a critical factor for the specification of the endocardial/endothelial and hematopoietic lineages [15,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 64%
“…Recently, it was shown that continued enforced expression of SOX7 in hemangioblast-derived blast colonies resulted in sustained expression of endothelial markers while impairing hematopoietic differentiation [37]. This same study implicated Cdh5, a gene known to be downstream of ETV2, as a direct downstream target of SOX7 [21,55]. Although there is significant overlap of Etv2 and Sox7 function in early endothelial and hematopoietic development, as well as apparent overlap of transcriptional pathways, a direct linkage between Etv2 and Sox7 has not previously been described.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In support of this, Gata-and ETS-binding sites are required for Etv2 expression in endothelial cells (Veldman and Lin, 2012;De Val et al, 2008); and Gata2 is the only Gata factor available for Etv2 activation and Fli1 the only ETS TF available. Finally, as Scl and Lmo2 require Etv2, which is required for contemporaneous Gata2 expression, the inputs of both into these genes are also likely to be direct, a conclusion supported in the case of Etv2 on Lmo2 by recent binding assays, albeit in the primitive haemangioblast (Koyano-Nakagawa et al, 2012).…”
Section: Research Articlementioning
confidence: 90%
“…[5][6][7][8] ER71 activates genes critical for both hematopoiesis and vessel development including Flk1, VECadherin (VE-Cad), Scl, and Lmo2 through direct binding to gene-associated promoters/enhancers. 5,[8][9][10] Studies in zebrafish and Xenopus also reported er71's potent function, 11,12 indicating an evolutionally conserved and essential role for ER71 in the establishment of the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%